Research progress of Ruyi Jinhuang Powder in the treatment of pressure injuries (如意金黄散治疗压力性损伤的研究进展) - ZHU Yuxin (朱雨昕); CHEN Gao (陈高); WANG Huifen (王惠芬) (中西医结合护理)
Pressure injury (PI) is a common skin problem that occurs most often in patients who are bedridden or have limited mobility, seriously affecting the quality of life of patients. In recent years, Traditional Chinese Medicine external treatment has gradually gained attention in the treatment of PI, and it has the unique advantage of regulating local Qi and blood circulation and promoting wound healing through external medication, acupuncture, massage, etc. This paper reviews the clinical use of Ruyi Jinhuang Powder in the treamten of PI from three aspects: an overview of the pathomechanism of PI, multi-target mechanisms of Ruyi Jinhuang Powder, and its clinical applications. This paper also points out the shortcomings of recent studies to provide new ideas for future studies. (压力性损伤(PI)是临床常见的皮肤问题, 多发于长期卧床或行动不便的患者, 严重影响患者的生活质量。近年来, 中医外治法在PI治疗中逐渐受到关注, 其通过外用药物、针灸、按摩等手段, 调节局部气血运行, 促进创面愈合, 具有独特优势。本研究系统综述了如意金黄散治疗PI的研究进展, 从PI的病理机制、如意金黄散的多靶点作用机制及其临床应用效果三个维度进行深入分析, 以期为该领域的后续研究提供理论依据和创新性研究方向。)